Ni-based overall water splitting electrocatalysts prepared via laser-ablation-in-liquids combined with electrophoretic deposition. (March 2022) - Shukla, A.; Singh, S.C.; Saraj, C.S.; Verma, G.; Guo, C.
Abstract: Synthesis of fine nanoparticles (NPs) with surface-active sites free from undesired chemical residues is the key to drive chemical kinetics. However, active sites of chemically produced NPs are limited because of the adsorption of chemical residues. Therefore, the development of a physical approach to produce NPs having surfaces free from chemical contamination is imperative to electrochemical water splitting. Here, we present a physical top-down approach where suspended NPs generated via pulsed laser ablation in liquids are electrophoretic deposited on a substrate to fabricate ready-to-use electrocatalysts for overall water splitting. Three different laser pulse energies were used to ablate Ni plate in pure water or aqueous media of 1M polyethylene glycol (PEG) to produce six different colloidal solutions of NPs. The samples produced in the water at higher laser pulse energies have Ni/NiO phase in abundance, while those produced in PEG dominate Ni/Ni(OH)2 phase. Among all the electrophoretically fabricated electrocatalysts, Ni-Di-70 is the best performer in overall water splitting, while Ni-P-30 is the worse. We believe that the selective adsorption of H∗, responsible for hydrogen evolution reaction, at Ni sites, and OH − ions, oxygen evolution intermediate, at NiO sites of Ni/NiO interface increase hydrogen and oxygen generation performances of Ni-Di-70 sample. The poor performance of PEG produced electrocatalysts is attributed to the combined effects of the formation of a larger assembly of NPs and adsorption of PEG molecules on the active sites. Graphical abstract: Image 1 Highlights: The laser pulse energy and liquid media-induced compositional control in Ni/NiO/Ni(OH)2 nanocomposite. Electrophoretic deposition to make ready-to-use electrocatalysts substrate from the colloidal solution of nanoparticles. About 10 2 -10 3 times better performance over corresponding catalysts produced in the polyethylene glycol solutions. Enhanced hydrogen evolution reaction and oxygen evolution reaction performances at the interface of the Ni/NiO.